Jian-Pi-Yi-Shen formula improves kidney function by regulating gut microbiome in rats with chronic kidney disease - Wang, Yuzhi; Lu, Jiandong; Dai, Wenkui; Yang, Shudong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionRecent studies have underscored the role of interactions between Traditional Chinese Medicine (TCM) and the gut microbiome (GM) in mediating therapeutic effects. Jian-Pi-Yi-Shen Formula (JPYSF) has shown efficacy in ameliorating chronic kidney disease (CKD) symptoms, but its mechanisms via GM modulation remain unclear.MethodsIn this study, 8-week-old rats were assigned to three groups after a two-week acclimation: C (normal diet for six weeks), M (adenine diet for four weeks then normal diet for two weeks), and T (same as M, with JPYSF administered during the final three weeks). Fecal samples were collected at three timepoints (T1: post-acclimation; T2: after three weeks on respective diets; T3: after three weeks of JPYSF treatment) for metagenomic sequencing. Serum creatinine (SCR) was measured at T2 and T3. ResultsAt T2, adenine-fed rats showed elevated SCR (C: 28.4 ± 1.5 µmol/L; M: 189.6 ± 25.8µmol/L; T: 186.4 ± 32.5µmol/L; p < 0.001). By T3, SCR decreased more in T (86.0 ± 14.9µmol/L) than in M (119.6 ± 16.3µmol/L; p = 0.012), with C remaining stable (30.8 ± 4.4µmol/L). Adenine feeding induced significant GM shifts, evidenced by increased Aitchison distance (p < 0.01) and altered co-abundance interaction groups (CIGs): CIG3, 6, 9, 10 increased; CIG1, 2, 4, 12 decreased (all p < 0.05). After JPYSF treatment, only CIG4 significantly rebounded (T3 vs. M, p = 0.0079), and T3-T1 dissimilarity was lower in T than M (p < 0.05). SCR levels were significantly lower in T than M after returning to a normal diet, suggesting a renoprotective effect of JPYSF. Co-occurrence analysis linked SCR positively with toxin-associated CIGs (CIG3, 6, 7, 9, 10) and pathways (purine metabolism, toluene degradation), and negatively with CIG4.DiscussionThese results demonstrate that JPYSF lowers SCR and selectively modulates GM modules, particularly CIG4, which inversely correlates with uremic toxin–producing pathways, suggesting improved renal function and specific gut microbiota modulation in CKD rats.